2018
DOI: 10.1016/j.triboint.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow across a wavy channel brought in contact

Abstract: A pressure driven flow in contact interface between elastic solids with wavy surfaces is studied. We consider a strong coupling between the solid and the fluid problems, which is relevant when the fluid pressure is comparable with the contact pressure. An approximate analytical solution is obtained for this coupled problem. A finite-element monolithically coupled framework is used to solve the problem numerically. A good agreement is obtained between the two solutions within the region of the validity of the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…Under the one-way coupling, which neglects the effect of the fluid pressure on the surface of the solid, the transmissivity of the interface is underestimated. Consequently, the critical pressure needed to seal the channel is higher if the two-way coupling is considered, which is an agreement with (Shvarts and Yastrebov, 2018a), where we found the critical sealing pressure to be an affine function of the inlet pressure for the case of a wavy channel without trapped fluid zone. Moreover, once a trapped fluid pool is formed, it provides additional load-bearing capacity, while its pressure is increasing with the increasing external load.…”
Section: Comparison Of the Interface Transmissivity Between One-and T...supporting
confidence: 90%
See 2 more Smart Citations
“…Under the one-way coupling, which neglects the effect of the fluid pressure on the surface of the solid, the transmissivity of the interface is underestimated. Consequently, the critical pressure needed to seal the channel is higher if the two-way coupling is considered, which is an agreement with (Shvarts and Yastrebov, 2018a), where we found the critical sealing pressure to be an affine function of the inlet pressure for the case of a wavy channel without trapped fluid zone. Moreover, once a trapped fluid pool is formed, it provides additional load-bearing capacity, while its pressure is increasing with the increasing external load.…”
Section: Comparison Of the Interface Transmissivity Between One-and T...supporting
confidence: 90%
“…The fluid pressure inside the lagoon before its closure is almost uniform and is higher than the mean value between the inlet and outlet fluid pressures (p in + p out )/2. This is also an effect of considering the two-way coupling, since the fluid pressure decrease from the inlet to the outlet is not linear (which is the case under one-way coupling), but is rather concave, as was shown in (Shvarts and Yastrebov, 2018a). At the second stage, see Fig.…”
Section: Fluid Flow Across a Wavy Channel With An "Atoll" Island And ...mentioning
confidence: 85%
See 1 more Smart Citation
“…To examine the exact contribution of shear stress applied on the fracture, more complex elastic–plastic models are required. First attempts going in this direction are the models of Yastrebov et al (2017) and those of Shvarts and Yastrebov (2018a, 2018b) where the problem is approached through spectral boundary element methods and full monolithic coupling of the mechanical deformation and hydraulic transport in the fractures. These methods should allow the extension to shear stress and plasticity (Frérot et al, 2019) with the geometries used in this study (grooves suborthogonal to fluid flow and shear sense as well as parallel ones).…”
Section: Effect Of Shear On Transmissivity: Extrapolation Of the Numementioning
confidence: 99%
“…This phenomenon can be explained by the linear elastic fracture mechanics (LEFM) theory [16]. So the fluid load must be considered for the cases where the fluid is present between the sealing surfaces [17,18]. In Reference [18], it was shown that a fully coupled approach considering the two-way fluid-structure interaction, between the sealing surfaces, is preferred compared with a sequential solution procedure, in which the equations are solved independently and the solution is obtained through iteration until convergence is reached.…”
Section: Introductionmentioning
confidence: 99%